Pengaruh TQM, Karakteristik Sia Dan Environmntal Uncertinty Terhadap Kinerja Manajerial Di Instansi Pemerintahan Daerah Kabupaten Jembrana - I Gusti Agung Ayu Ngurah Sri Novita Dewi; Sang Ayu Putu Arie Indraswarawati (Hita Akuntansi dan Keuangan, 2023)
Leadership performance is work done by a person in leadership roles. The aim of this research is to pointing the effects of TQM on managerial performance in Jembrana Regency government agencies in the quality of public services. The 100 people interviewed for this study were leaders who worked in regional apparatus organizations, such as service heads, division heads, section heads, and section heads in Jembrana district government agencies. The purposive sampling method is used to determine the sample. Artificial analysis has shown that tqm has a positive and relevant to management performance variables. There is no evidence to suggest that the characteristics SIA have any significant impact on managerial performance or environmental sustainability. uncertainty does not have significant impact on the managerial effectiveness variable.